Numerical analysis of the broadband interferometric sensor in the planar gradient-step index configuration - Blahut, Marek (Photonics Letters of Poland, 2022)
In the paper the model of an optical sensor based on a two-mode interference in a planar gradient-step index configuration is presented. The analyzed structure consists of a single-mode gradient index waveguide, made by Ag+-Na+ ion exchange, which is partially covered by a step-index SU-8 polymer layer. This step and gradient index structure forms a two-mode waveguide which is excited by a broadband light source from a selected spectral range. The refractive index variation of measured external surrounding affects the modal properties of multimode waveguide and the spectral field distribution at the output of the structure. Full Text: PDF References M. Błahut, "Numerical analysis of planar multimode optical sensor with active nanolayer", Opt. Appl. 50, 377 (2020). CrossRef M. Nordstrom et al J. Light. Technol. 25, 1284 (2007). CrossRef K. Gut, "Study of a Broadband Difference Interferometer Based on Low-Cost Polymer Slab Waveguides", Nanomaterials, 9, 729 (2019). CrossRef M. Błahut, "Numerical characteristics of the polarimetric interferometer made by K+-Na+ ion exchange", Opt. Appl. 27, 3 (1998). CrossRef https://www.filmetrics.com/refractive-index-database/BK7/Float-Glass DirectLink M. Błahut, "Model of the broadband interferometric optical biosensor in a planar configuration", Phot. Lett. Pol. 12, 28 (2020). CrossRef K. Gut, "Broad-band difference interferometer as a refractive index sensor", Opt. Express, 25, 31111 (2017). CrossRef